Numerical analysis of three-dimensional arch-bank slope based on fluid–structure interaction - Yuexing Wu; Kai Shen; Xinzhong Wang; Yi Xiang; Linshu Li (Journal of Engineering and Applied Science)
Abstract The large-span arch bridge constructed in the reservoir area often requires the setting of its arch abutments on steep reservoir banks, which are subject to the long-term fluctuation of water levels in the river channel, facing potential risks of instability. Taking the Guizhou Luowang River Extra Large Bridge as the engineering background, this paper establishes reasonable full-bridge model and three-dimensional arch-bank model based on the effective stress principle and Forchheimer’s law using the finite element software MIDAS/Civil and ABAQUS, respectively, for numerical simulation analysis. A two-step finite element analysis method and finite element strength reduction method are employed to analyze the influence of water level factors on the stability of the Guizhou Luowang River Extra Large Bridge arch-bank. Considering the contact interaction between the arch and the bank slope, the stability, internal forces, and deformation characteristics of the arch-bank under different seepage conditions are analyzed, with emphasis on the steady-state seepage under normal, maximum, and minimum water levels, as well as the transient seepage caused by sudden changes in water level with different flow velocities. The research results indicate the significant importance of studying the influence of water level changes on the stability of arch-bank.